Sphingosine-1-phosphate as an indicator for deciding the use of adjuvant corticosteroids therapy in community-acquired pneumonia (sphingosine-1-phosphate and pneumonia trial): Study protocol for a randomized, placebo-controlled trial. Issue 38 (September 2019) - Hsu, Shih-Chang; Huang, Wen-Cheng; Liu, Chung-Te; Hsu, Yuan-Pin; Chang, Jer-Hwa; Huang, Shau-Ku; Hsu, Chin-Wang
Abstract: Introduction: Pneumonia is one of the leading causes of death worldwide, represents a potentially life-threatening condition. In recent studies, adjuvant corticosteroids therapy has been shown to improve outcome in severe community-acquired pneumonia (CAP); however, the treatment response to corticosteroids vary. It is important to select patients likely to benefit from the treatment. Currently, the optimal patient selection of corticosteroids treatment is not yet clearly defined. Methods: Sphingosine-1-phosphate and pneumonia (SOPN) trial is a double-blinded, randomized, placebo-controlled trial that will investigate if sphingosine-1-phosphate (S1P) can be an indicator for initiating adjuvant corticosteroids therapy in patients with severe CAP. Participants will be recruited from the emergency department and randomized to receive 20 mg of methylprednisolone twice daily or placebo for 5 days. The primary outcome will be "in-hospital mortality." Secondary outcomes will include intensive care unit (ICU) admission, length of ICU stay, length of hospital stay, and clinical outcomes at Day 7 and Day 14. Conclusion: SOPN trial is the first randomized placebo-controlled trial to investigate whether S1P can be a predictive biomarker for adjuvant corticosteroids therapy in patients with severe CAP. The trial will add additional data for the appropriate use of adjuvant corticosteroids therapy in patients with severe CAP. Results from this clinical trial will provide foundational information supporting that if the S1P is appropriate for guiding the patient selection for corticosteroids adjuvant therapy.